Handle reaction forces in handcycling on an ergometer - Viellehner, J.; Funken, J.; Wolbert, F. A. J.; Peters, M.; Potthast, W. (ISBS Proceedings Archive (Michigan), 2017)
The purpose of this study was to develop a three dimensional sensitive dynamometric handcycling grip and to examine the influence of grip positioning on hand contact forces during low resistance arm cranking. Contact forces of ten male subjects were measured at a neutral grip position, increased crank arm length and increased grip width. The findings suggest a pushdown-pull cranking pattern. Therefore shoulder extensors and elbow flexors may have an important role in force generation. Changes at the grip position have a clear effect on grip contact forces, thus the interaction is complex due to subject specific variations. The data sets the basis for an inverse dynamic model and provides information about involved muscles which is helpful for the training process and injury prevention.